What is AI Ethics? Ethics as means of self-regulation and the need for critical reflection - Alpsancar, Suzana (International Conference on Computer Ethics 2023)

Optimized, Highly Efficient Silicon Antennas for Optical Phased Arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
Silicon photonics, in conjunction with complementary metal-oxide-semiconductor (CMOS) fabrication, has greatly enhanced the development of integrated optical phased arrays. This facilitates a dynamic control of light in a compact form factor that enables the synthesis of arbitrary complex wavefronts in the infrared spectrum. We numerically demonstrate a large-scale two-dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing elegant radiation patterns in the far-field. For a wavelength of 1.55 μm, we optimize two antennas for the OPA exhibiting an upward radiation efficiency as high as 90%, with almost 6.8% of optical power concentrated in the field of view. Additionally, we believe that the proposed OPAs can be easily fabricated and would have the ability to generate complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation, and augmented-reality displays.
Keywords: tet_topic_opticalantenna

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.
Keywords: tet_topic_qd

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

Softsensors: key component of property control in forming technology - Homberg, Werner; Arian, Bahman; Arne, Viktor; Borgert, Thomas; Brosius, Alexander; Groche, Peter; Hartmann, Christoph; Kersting, Lukas; Laue, Robert; Martschin, Juri; Meurer, Thomas; Spies, Daniel; et al. (Production Engineering)
Abstract The constantly increasing challenges of production technology for the economic and resource-saving production of metallic workpieces require, among other things, the optimisation of existing processes. Forming technology, which is confronted with new challenges regarding the quality of the workpieces, must also organise the individual processes more efficiently and at the same time more reliably in order to be able to guarantee good workpiece quality and at the same time to be able to produce economically. One way to meet these challenges is to carry out the forming processes in closed-loop control systems using softsensors. Despite the many potential applications of softsensors in the field of forming technology, there is still no definition of the term softsensor. This publication therefore proposes a definition of the softsensor based on the definition of a sensor and the distinction from the observer, which on the one hand is intended to stimulate scientific discourse and on the other hand is also intended to form the basis for further scientific work. Based on this definition, a wide variety of highly topical application examples of various softsensors in the field of forming technology are given.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Zwischen Überwältigung und Beliebigkeit - Wertorientierung im Unterricht als Aufgabe der Lehrpersonenbildung - Schlegel-Matthies, Kirsten (Nachdenken über Lehrerinnen- und Lehrerbildung. Anregungen zur Weiterentwicklung der Pädagogischen Hochschulen in der deutschsprachigen Schweiz. Aus Anlass des 20-Jahre-Jubiläums der Pädagogischen Hochschule Luzern)

Open Research Practices and Cultural Change: A Commentary on “(Why) Are Open Research Practices the Future for the Study of Language Learning?” - Steinhardt, Isabel; Mauermeister, Sylvi; Schmidt, Rebecca (Language Learning)
Keywords: Open Science; Open Science Practices; Cultural Change

The Bot Delusion. ChatGPT and anticipated consequences for research communication - Wieczorek, Oliver; Steinhardt, Isabel; Schneijderberg, Christian; Schmidt, Rebecca; Mauermeister, Sylvi
The reproduction of social inequalities through artificial intelligence (AI) and machine learning via artificial neural networks (ANN) has been demonstrated empirically in various areas of society, for instance in policing and personnel hiring decisions. Yet, a broader discussion is missing to what extent ANN technological developments may affect the scientific enterprise and reinforce or mitigate existing structural inequalities in academia. Focusing on publications and citations as main currencies in science, the anticipated consequences of ChatGPT on the research communication of existing and new knowledges are discussed in three scenarios, which echo the social structures in academia.

Discrete Lagrangian Neural Networks with Automatic Symmetry Discovery - Lishkova, Yana; Scherer, Paul; Ridderbusch, Steffen; Jamnik, Mateja; Liò, Pietro; Ober-Blöbaum, Sina; Offen, Christian (IFAC-PapersOnLine)
By one of the most fundamental principles in physics, a dynamical system will exhibit those motions which extremise an action functional. This leads to the formation of the Euler-Lagrange equations, which serve as a model of how the system will behave in time. If the dynamics exhibit additional symmetries, then the motion fulfils additional conservation laws, such as conservation of energy (time invariance), momentum (translation invariance), or angular momentum (rotational invariance). To learn a system representation, one could learn the discrete Euler-Lagrange equations, or alternatively, learn the discrete Lagrangian function Ld which defines them. Based on ideas from Lie group theory, in this work we introduce a framework to learn a discrete Lagrangian along with its symmetry group from discrete observations of motions and, therefore, identify conserved quantities. The learning process does not restrict the form of the Lagrangian, does not require velocity or momentum observations or predictions and incorporates a cost term which safeguards against unwanted solutions and against potential numerical issues in forward simulations. The learnt discrete quantities are related to their continuous analogues using variational backward error analysis and numerical results demonstrate the improvement such models can have both qualitatively and quantitatively even in the presence of noise.

Politisierung von Jugend

Intersektionalität und erzählte Welten. Fachwissenschaftliche und fachdidaktische Perspektiven auf Literatur und Medien
Der vorliegende Band versammelt intersektionale literaturwissenschaftliche und -didaktische Fallstudien aus unterschiedlichen Philologien und bietet so ein Prisma der Erforschung literarischer Repräsentationen des Zusammenspiels von einander verschärfenden bzw. abschwächenden Diskriminierungskategorien. Die Einzelbeiträge präsentieren kritische Reflexionen und Modifizierungen verschiedener Positionen der intersektionalen Forschung sowie Beispiele für die vielfältige Ausgestaltung intersektional orientierter Textanalyse auf theoretischer und methodischer Ebene. Da wissenschaftliche und literarische ebenso wie zeitgenössische und historische Texte in verschiedenen Sprachen (Englisch, Deutsch, Italienisch, Niederländisch, Spanisch etc.) aufgegriffen werden, zeigt der Band auf, dass Machtstrukturen in unterschiedlichen kulturellen Kontexten Analogien aufweisen, deren Analyse von Differenzierungen verschiedener Herrschaftsstrukturen profitiert.
Keywords: Intersektionalität; Literaturwissenschaft; Literaturunterricht; Klassenlektüre; Auswahl; Textanalyse; Literatur; Erzähltheorie; Machtstruktur; Diskriminierung; Geschlechterrolle; Geschlechterverhältnis; Geschlechtsidentität; Rassismus; Soziale Klasse; Othering; Feminismus

A Marxist-Humanist Perspective on Stuart Hall's Communication Theory - Fuchs, Christian (Theory and Society)

Designbasierte Forschung in der beruflichen Bildung:Perspektiven aus Wissenschaft, Praxis und Politik. - Ertl, Hubert; Kremer, H.-Hugo; Kundisch, Heike; Sloane, Peter F. E. (Wissenschaft trifft Praxis - Designbasierte Forschung in der beruflichen Bildung.)
Designbasierte Forschung umfasst verschiedene Ausprägungsformen von Forschungsprozessen, die auf die Entwicklung und Implementation von Innovationen abzielen. Mit der Anwendung von designbasierten Ansätzen haben Forscherinnen und Forscher den Anspruch, sich an der Lösung praktischer Problemlagen zu beteiligen; dies ist ein wichtiger Ausgangspunkt für die Anlage von Forschungsprozessen und -programmen. Häufig geht es um bisher wenig strukturierte, aktuelle Probleme in der Berufsbildungspraxis, was wiederum bedeutsam für das Aufeinandertreffen und die Zusammenarbeit von Wissenschaft und Praxis ist. Der vorliegende Band nimmt die Vielfalt designbasierter Forschung auf und dokumentiert, ergänzt durch Visualisierungen, die Beiträge des AG BFN Forums „Wissenschaft trifft Praxis – Designbasierte Forschung in der beruflichen Bildung“, welches in einem digitalen Format an der Universität Paderborn stattfand.

Wie wir die mittlere Führungsebene als Transformationsbegleiter:innen an Schulen stärken können - Kundisch, Heike (Magazin des Forum Bildung Digitalisierung)

Hall mobilities and sheet carrier densities in a single LiNbO3 conductive ferroelectric domain wall - Beccard, Henrik; Beyreuther, Elke; Kirbus, Benjamin; Seddon, Samuel D.; Rüsing, Michael; Eng, Lukas M. (Physical Review Applied)
In the last decade, conductive domain walls (CDWs) in single crystals of the uniaxial model ferroelectric lithium niobate (LiNbO3; LNO) have been shown to reach resistances more than 10 orders of magnitude lower than the resistance of the surrounding bulk, with charge carriers being firmly confined to sheets with a width of a few nanometers. LNO is thus currently witnessing increased attention because of its potential in the design of room-temperature nanoelectronic circuits and devices based on such CDWs. In this context, the reliable determination of the fundamental transport parameters of LNO CDWs, in particular the 2D charge carrier density n2D and the Hall mobility μH of the majority carriers, is of great interest. In this contribution, we present and apply a robust and easy-to-prepare Hall-effect measurement setup by adapting the standard four-probe van der Pauw method to contact a single, hexagonally shaped domain wall that fully penetrates the 200-μm-thick LNO bulk single crystal. We then determine n2D and μH for a set of external magnetic fields B and prove the expected cosinelike angular dependence of the Hall voltage. Lastly, we present photoinduced-Hall-effect measurements of one and the same DW, by determining the impact of super-band-gap illumination on n2D.
Keywords: General Physics and Astronomy

Do People Recover from Algorithm Aversion? An Experimental Study of Algorithm Aversion over Time - Leffrang, Dirk; Bösch, Kevin; Müller, Oliver (Hawaii International Conference on System Sciences)
Optimal decision making requires appropriate evaluation of advice. Recent literature reports that algorithm aversion reduces the effectiveness of predictive algorithms. However, it remains unclear how people recover from bad advice given by an otherwise good advisor. Previous work has focused on algorithm aversion at a single time point. We extend this work by examining successive decisions in a time series forecasting task using an online between-subjects experiment (N = 87). Our empirical results do not confirm algorithm aversion immediately after bad advice. The estimated effect suggests an increasing algorithm appreciation over time. Our work extends the current knowledge on algorithm aversion with insights into how weight on advice is adjusted over consecutive tasks. Since most forecasting tasks are not one-off decisions, this also has implications for practitioners.
Keywords: Algorithm aversion; Time series; Decision making; Advice taking; Forecasting

Event Recommendations through the Lens of Vision and Language Foundation Models - Halimeh, Haya; Freese, Florian; Müller, Oliver (Workshop on Recommenders in Tourism, co-located with the 17th ACM Conference on Recommender Systems)
Recommender systems now span the entire customer journey. Amid the multitude of diversified experi- ences, immersing in cultural events has become a key aspect of tourism. Cultural events, however, suffer from fleeting lifecycles, evade exact replication, and invariably lie in the future. In addition, their low standardization makes harnessing historical data regarding event content or past patron evaluations intricate. The distinctive traits of events thereby compound the challenge of the cold-start dilemma in event recommenders. Content-based recommendations stand as a viable avenue to alleviate this issue, functioning even in scenarios where item-user information is scarce. Still, the effectiveness of content- based recommendations often hinges on the quality of the data representation they build upon. In this study, we explore an array of cutting-edge uni- and multimodal vision and language foundation models (VL-FMs) for this purpose. Next, we derive content-based recommendations through a straightforward clustering approach that groups akin events together, and evaluate the efficacy of the models through a series of online user experiments across three dimensions: similarity-based evaluation, comparison-based evaluation, and clustering assignment evaluation. Our experiments generated four major findings. First, we found that all VL-FMs consistently outperformed a naive baseline of recommending randomly drawn events. Second, unimodal text-based embeddings were surprisingly on par or in some cases even superior to multimodal embeddings. Third, multimodal embeddings yielded arguably more fine-grained and diverse clusters in comparison to their unimodal counterparts. Finally, we could confirm that cross event interest is indeed reliant on the perceived similarity of events, resonating with the notion of similarity in content-based recommendations. All in all, we believe that leveraging the potential of contemporary FMs for content-based event recommendations would help address the cold-start problem and propel this field of research forward in new and exciting ways.

Early Depression Detection with Transformer Models: Analyzing the Relationship between Linguistic and Psychology-Based Features - Halimeh, Haya; Caron, Matthew; Müller, Oliver (Hawaii International Conference on System Sciences)
Clinical depression is a serious mental disorder that poses challenges for both personal and public health. Millions of people struggle with depression each year, but for many, the disorder goes undiagnosed or untreated. Over the last decade, early depression detection on social media emerged as an interdisciplinary research field. However, there is still a gap in detecting hesitant, depression-susceptible individuals with minimal direct depressive signals at an early stage. We, therefore, take up this open point and leverage posts from Reddit to fill the addressed gap. Our results demonstrate the potential of contemporary Transformer architectures in yielding promising predictive capabilities for mental health research. Furthermore, we investigate the model’s interpretability using a surrogate and a topic modeling approach. Based on our findings, we consider this work as a further step towards developing a better understanding of mental eHealth and hope that our results can support the development of future technologies.
Keywords: Social Media and Healthcare Technology; early depression detection; liwc; mental health; transfer learning; transformer architectures

Investigation of the influence of process parameters on productivity in the LPBF process for the material Inconel 718 - Bödger, Christian; Gnaase, Stefan; Lehnert, Dennis; Tröster, Thomas (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference)
The nickel-based alloy Inconel 718, which is used in aerospace technology, poses a great challenge to conventional machining due to its high strain hardening and toughness. Here, the laser powder bed fusion process (LPBF) offers an alternative with potential savings if sufficiently high productivity can be achieved. Based on the parameter study carried out, starting from the SLM Solutions standard parameters for the manufacturing of components, exposure parameters could be developed to realize manufacturing with 120 μm and 150 μm layer thickness, with almost the same geometric accuracy. For this purpose, the process parameters of laser power, focus diameter, hatch distance and scan speed were varied. The negative defocusing of the laser showed a positive effect on the density of the parts, realizing densities ≥ 99.94 %, with high dimensional stability and good mechanical properties. Considering the reduced manufacturing time of up to 61 %, a significant increase in productivity was achieved.

Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen - Spiller, Achim; Nieberg, Hiltrud; Renner, Britta; Balmann, Alfons; Birna, Regina; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; Götz, Kai-Uwe; Linseisen, Jakob; Nöthlings, Ute; et al.
Zitieren als: Wissenschaftlicher Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucher- schutz beim BMEL (2023): Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen. Gutachten. Berlin.

Qualitätsmanagement im Verbundvorhaben Communities of Practice für eine innovative Lehrerbildung NRW (COMeIN). Abschlussbericht - Buhl, Heike M.; Eickelmann, Birgit; Niemann, Jan; Raneck-Kuhlmann, Anna; Drossel, Kerstin

"Immerhin wurden Erfahrungen mit digitalen Tools gemacht" - Mauermeister, Sylvi; Steinhardt, Isabel; Bloch, Roland; Lohner, David; Schulz, Anja (Sozialmagazin)
Der Hoffnung auf einen nachhaltigen Digitalisierungsschub von Studium und Lehre an Hochschulen in Corona-Zeiten folgte vielerorts Ernüchterung. Die fast vollständige und überwiegend begrüßte Rückkehr zur Präsenzlehre führte dazu, dass wenig darüber reflektiert wurde, welche Erfahrungen mit der Online-Lehre gemacht wurden und worauf sich aufbauen lässt. Im Frühjahr 2023 wurde ein Open-Space-Workshop zur Unterstützung der (digitalen) Lehre durchgeführt. Die Ergebnisse zeigen: Den Lehrenden kommt eine zentrale Rolle für die weitere Digitalisierung zu.

Gelingensbedingungen der phasenübergreifenden Zusammenarbeit in der Lehrkräftebildung zur Entwicklung digitalisierungsbezogener Ressourcen in Communities of Practice - Niemann, Jan; Drossel, Kerstin; Eickelmann, Birgit; Raneck-Kuhlmann, Anna; Buhl, Heike M. (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Im Zuge der digitalen Transformation der Gesellschaft steht die Lehrkräftebildung vor der Herausforderung, (angehenden) Lehrkräften Kompetenzen zu vermitteln, um schulische Lehr-Lernprozesse zeitgemäß zu gestalten. Eine Möglichkeit liegt dabei in der Entwicklung theoretisch fundierter und praxisorientierter digitalisierungsbezogener Ressourcen, die für diese Zwecke genutzt werden können. Um solche Ressourcen zu entwickeln, erscheint der Ansatz der phasenübergreifenden Zusammenarbeit in Communities of Practice (CoPs) der Lehrkräftebildung vielversprechend, da hier die Expertise aller Phasen genutzt werden kann. Bisherige Forschungsergebnisse zu Gelingensbedingungen der Zusammenarbeit lassen auf Faktoren wie Zielorientierung, Aufgabenbewältigung, Zusammenhalt oder Verantwortungsübernahme schließen, beziehen sich jedoch überwiegend auf Teams im Allgemeinen oder CoPs aus dem Wirtschaftskontext. Bisher unerforscht sind damit Gelingensbedingungen für die phasenübergreifende Zusammenarbeit in der Lehrkräftebildung, weshalb der vorliegende Beitrag diese Thematik untersucht. Zur Bearbeitung dieses Forschungsdesiderates werden quantitative und qualitative Daten aus dem COMeIN-Verbundvorhaben (Communities of Practice für eine innovative Lehrkräftebildung in NRW) herangezogen. Mittels einer multiplen Regressionsanalyse wurde die Aufgabenbewältigung in den CoPs als zentraler Prädiktor für positiv wahrgenommene phasenübergreifende Zusammenarbeit identifiziert. Die qualitative Inhaltsanalyse verdeutlicht zudem u.a. die hohe Relevanz der Beachtung der unterschiedlichen Systemlogiken der lehrkräfte-bildenden Phasen. Die Ergebnisse können dazu beitragen, die Zusammenarbeit der lehrkräftebildenden Phasen in CoPs zu verbessern, um so gesellschaftliche Transformationen in der Lehrkräftebildung adäquat mitzugestalten.

When Do Firms Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren (Accounting and Business Research)
This study examines GAAP effective tax rate (ETR) visibility as a distinct disclosure choice in firms’ financial statements. By applying a game-theory disclosure model for the voluntary disclosure strategies of firms, in a tax setting, we argue that firms face a trade-off in their ETR disclosure decisions. On the one hand, firms have an incentive to enhance their ETR disclosure when the ratio offers shareholders ‘favourable conditions’, for example, higher expected after-tax cash flows. On the other hand, the disclosure of a favourable low ETR could attract the attention of tax auditors and the public and ultimately result in disclosure costs. We empirically test disclosure behaviour by examining the relation between disclosure visibility and different ETR conditions that reflect different stakeholder-specific costs and benefits. While we find that unfavourable ETR conditions are not highlighted, we observe higher disclosure visibility for favourable ETRs (smooth, close to the industry average, and decreasing ETRs). Additional analyses reveal that this high visibility is characteristic of firm years with only moderately decreasing ETRs at usual ETR levels, while extreme ETRs are not highlighted. Interestingly and in contrast to our main results, a subsample of family firms does not seem to highlight favourable ETRs.

Losses Never Sleep – The Effect of Tax Loss Offset on Stock Market Returns during Economic Crises - Koch, Reinald; Holtmann, Svea; Giese, Henning (Journal of Business Economics)

The Tax Complexity Index – A Survey-Based Country Measure of Tax Code and Framework Complexity - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (European Accounting Review)

Schultransform trifft MINT. Der Einfluss eines MINT-Schwerpunkts auf die Schultransformation - Schulte, A.; Eickelmann, Birgit; Hauck-Thum, U.

“The Morality of Self-Acceptance: La Rochefoucauld and the Augustinian Challenge.” - Blank, Andreas (Early Modern French Studies)

“Marquard Freher and the Presumption of Goodness in Legal Humanism.” - Blank, Andreas (History of European Ideas)

A multiobjective continuation method to compute the regularization path of deep neural networks - Amakor, Augustina Chidinma; Sonntag, Konstantin; Peitz, Sebastian (arXiv)
Sparsity is a highly desired feature in deep neural networks (DNNs) since it ensures numerical efficiency, improves the interpretability of models (due to the smaller number of relevant features), and robustness. In machine learning approaches based on linear models, it is well known that there exists a connecting path between the sparsest solution in terms of the $\ell^1$ norm,i.e., zero weights and the non-regularized solution, which is called the regularization path. Very recently, there was a first attempt to extend the concept of regularization paths to DNNs by means of treating the empirical loss and sparsity ($\ell^1$ norm) as two conflicting criteria and solving the resulting multiobjective optimization problem. However, due to the non-smoothness of the $\ell^1$ norm and the high number of parameters, this approach is not very efficient from a computational perspective. To overcome this limitation, we present an algorithm that allows for the approximation of the entire Pareto front for the above-mentioned objectives in a very efficient manner. We present numerical examples using both deterministic and stochastic gradients. We furthermore demonstrate that knowledge of the regularization path allows for a well-generalizing network parametrization.

Error analysis of kernel EDMD for prediction and control in the Koopman framework - Philipp, Friedrich; Schaller, Manuel; Worthmann, Karl; Peitz, Sebastian; Nüske, Feliks (arXiv:2312.10460)
Extended Dynamic Mode Decomposition (EDMD) is a popular data-driven method to approximate the Koopman operator for deterministic and stochastic (control) systems. This operator is linear and encompasses full information on the (expected stochastic) dynamics. In this paper, we analyze a kernel-based EDMD algorithm, known as kEDMD, where the dictionary consists of the canonical kernel features at the data points. The latter are acquired by i.i.d. samples from a user-defined and application-driven distribution on a compact set. We prove bounds on the prediction error of the kEDMD estimator when sampling from this (not necessarily ergodic) distribution. The error analysis is further extended to control-affine systems, where the considered invariance of the Reproducing Kernel Hilbert Space is significantly less restrictive in comparison to invariance assumptions on an a-priori chosen dictionary.

Adaptive Koopman-Based Models for Holistic Controller and Observer Design - Junker, Annika; Pape, Keno Egon Friedrich; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: General Medicine

Umfrage: Tax Compliance und Verrechnungspreise - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren

Wissenschaftsbezogener Rechtspopulismus/-extremismus an Hochschulen – Perspektiven von Betroffenen - Haker, Christoph; Otterspeer, Lukas (ZRex – Zeitschrift für Rechtsextremismusforschung)
Mit dem Begriff wissenschaftsbezogener Rechtspopulismus/-extremismus fokussiert der Beitrag solche (extrem) rechten Organisationen, Praktiken und Diskursstrategien, die sich auf das Feld der Wissenschaft beziehen. Dabei rückt in einer qualitativen Interview-Studie die Betroffenenperspektive in den Mittelpunkt, die ein blinder Fleck der Forschung ist: Wie nehmen Betroffene wissenschaftsbezogenen Rechtspopulismus/-extremismus wahr und welche Umgangsweisen finden sie? Präsentiert werden Ergebnisse zur widersprüchlichen Erscheinungsform von wissenschaftsbezogenem Rechtspopulismus/-extremismus. Neben erwartbaren Phänomenen (zum Beispiel (kultur-)rassistischen, misogynen, antidemokratischen und verschwörungstheoretischen Positionierungen) zeigt sich dieser insofern widersprüchlich, als dass er zwischen Inanspruchnahme von Wissenschaftlichkeit sowie Wissenschaftsfreiheit auf der einen Seite und Wissenschaftsfeindlichkeit auf der anderen Seite oszilliert. Er trifft mit Hochschulen auf Institutionen, deren Strukturen einen kritischen Umgang erschweren, und er wirkt weit über die jeweils konkreten Situationen seines Erscheinens hinaus. Unsere Analysen untermauern die Notwendigkeit, die Bedeutung von wissenschaftsbezogenem Rechtspopulismus/-extremismus in seiner Widersprüchlichkeit über die jeweiligen Situationen hinaus zu erkennen und wissenschaftsspezifische Antworten zu finden, die dieser Widersprüchlichkeit Rechnung tragen – und sind damit eine Aufforderung an Hochschulen und alle dort tätigen Personen.

Einladung zum Draußen-Bleiben. Safer Spaces sind nicht nur Schutzraum, sie sind eine Methode der Herrschafts- und Erkenntniskritik. - Haker, Christoph; Otterspeer, Lukas; Thole, Werner

Wie hältst du es mit der Wahrheit? Bilder von Wissenschaft und Wissenschaftler*in-Sein angesichts von Diagnosen der Postfaktizität. - Haker, Christoph; Otterspeer, Lukas (Entgrenzungen. Beiträge zum 28. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft)

Wissenschaftsbezogener Rechtspopulismus/-extremismus. Eine Podiumsdiskussion. - Haker, Christoph; Lehnert, Esther; Otterspeer, Lukas; Thole, Werner (Polarisierte Welten. Verhandlungen des 41. Kongresses der Deutschen Gesellschaft für Soziologie in Bielefeld 2022)

Decision Support Ecosystems: Assisted Low-Code Development of Tailored Decision Support Systems - Kirchhoff, Jonas
Erfolg und Misserfolg eines Unternehmens werden maßgeblich durch getroffene Entscheidungen beeinflusst. Daher verlassen sich Entscheider oft auf Entscheidungsunterstützungssysteme, die durch Datensimulation, -optimierung und -visualisierung bei der Identifizierung von geeigneten Entscheidungen unterstützen. Für eine optimale Unterstützung muss ein Entscheidungsunterstützungssystem (EUS) jedoch auf den Entscheidungsprozess eines Entscheiders abgestimmt sein und verfügbare Daten, Optimierungsziele, persönliche Präferenzen sowie weitere Einflussfaktoren berücksichtigen. EUS-Entwickler können aufgrund der Komplexität und Volatilität von Geschäftsumgebungen allerdings nicht alle potenziellen Entscheidungsprozesse während des Entwurfs eines EUS vorhersehen, wodurch ein EUS einem Entscheider häufig nur unzureichende Anpassungsmöglichkeiten an den individuellen Entscheidungsprozess bietet. Die Einzelanfertigung eines EUS, das auf einen Entscheidungsprozess zugeschnitten ist, ist ein kosten- und zeitintensives Unterfangen aufgrund der begrenzten Verfügbarkeit von Softwareentwicklern oder Missverständnissen zwischen Entwicklern und Entscheidern während der Entwicklung. Daher geben sich Entscheider möglicherweise mit einem handelsüblichen EUS zufrieden, das nicht vollständig mit ihrem Entscheidungsprozess übereinstimmt, suboptimale Entscheidungen begünstigt und so den Unternehmenserfolg negativ beeinflusst. In dieser Arbeit wird ein Ansatz vorgeschlagen, der es Entscheidern ermöglicht, selbst maßgeschneiderte Entscheidungsunterstützungssysteme zu entwickeln und so die Diskrepanz zwischen benötigter und tatsächlicher Entscheidungsunterstützung zu vermeiden. Dazu stellen EUS-Entwickler einen Teil der EUS-Funktionalität als wiederverwendbare Software-Dienste bereit ...

Intersektionalität und erzählte Welten
Intersektionalität hält als Forschungsgegenstand, als Schauplatz theoretischer Diskussion und als Analyseperspektive seit Jahren verstärkt Einzug in unterschiedliche akademische Disziplinen und Bereiche. Es verwundert daher nicht, dass sich das Intersektionalitätsparadigma auch im Bereich der Literaturwissenschaft und -didaktiken zunehmend als produktiv erweist, wie wir mit dem Sammelband zeigen wollen, der intersektionale literaturwissenschaftliche und -didaktische Fallstudien aus unterschiedlichen Philologien versammelt und so ein Prisma der Erforschung literarischer Repräsentationen des Zusammenspiels von einander verschärfenden bzw. abschwächenden Diskriminierungskategorien bietet. Inwiefern die Einzelbeiträge kritische Reflexionen verschiedener Positionen der Intersektionalitätsforschung präsentieren und Beispiele für die vielfältige Ausgestaltung intersektional orientierter Textanalyse auf theoretischer und methodischer Ebene anbieten sowie didaktische Lesarten des Intersektionalitätsparadigmas aufzeigen, machen wir aufbauend auf einer ausführlichen Begriffs- und Theoriereflexion einleitend deutlich.

A pairing formula for resonant states on finite regular graphs - Hilgert, Joachim; Arends, C.; Frahm, J.

Edge Laplacians and vector valued Poisson transforms for graphs - Hilgert, Joachim; Arends, C.; Frahm, J.

Quantization in fibering polarizations, Mabuchi rays and geometric Peter--Weyl theorem - Hilgert, Joachim; Baier, T.; Kaya, O.; Mourao, J.; Nunes, J.

Ruelle-Taylor resonances of Anosov actions - Hilgert, Joachim; Guedes Bonthonneau, Y.; Guillarmou, C.; Weich, Tobias

Fast Convergence of Inertial Multiobjective Gradient-like Systems with Asymptotic Vanishing Damping - Sonntag, Konstantin; Peitz, Sebastian (arXiv:2307.00975)
We present a new gradient-like dynamical system related to unconstrained convex smooth multiobjective optimization which involves inertial effects and asymptotic vanishing damping. To the best of our knowledge, this system is the first inertial gradient-like system for multiobjective optimization problems including asymptotic vanishing damping, expanding the ideas laid out in [H. Attouch and G. Garrigos, Multiobjective optimization: an inertial approach to Pareto optima, preprint, arXiv:1506.02823, 201]. We prove existence of solutions to this system in finite dimensions and further prove that its bounded solutions converge weakly to weakly Pareto optimal points. In addition, we obtain a convergence rate of order O(t−2) for the function values measured with a merit function. This approach presents a good basis for the development of fast gradient methods for multiobjective optimization.

Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Bernreuther, Marco; Dellnitz, Michael; Gebken, Bennet; Müller, Georg; Peitz, Sebastian; Sonntag, Konstantin; Volkwein, Stefan (arXiv:2308.01113)
Multiobjective optimization plays an increasingly important role in modern applications, where several criteria are often of equal importance. The task in multiobjective optimization and multiobjective optimal control is therefore to compute the set of optimal compromises (the Pareto set) between the conflicting objectives. The advances in algorithms and the increasing interest in Pareto-optimal solutions have led to a wide range of new applications related to optimal and feedback control - potentially with non-smoothness both on the level of the objectives or in the system dynamics. This results in new challenges such as dealing with expensive models (e.g., governed by partial differential equations (PDEs)) and developing dedicated algorithms handling the non-smoothness. Since in contrast to single-objective optimization, the Pareto set generally consists of an infinite number of solutions, the computational effort can quickly become challenging, which is particularly problematic when the objectives are costly to evaluate or when a solution has to be presented very quickly. This article gives an overview of recent developments in the field of multiobjective optimization of non-smooth PDE-constrained problems. In particular we report on the advances achieved within Project 2 "Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Switches, State Constraints and Model Order Reduction" of the DFG Priority Programm 1962 "Non-smooth and Complementarity-based Distributed Parameter Systems: Simulation and Hierarchical Optimization".

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Cancel Culture als Arena politisierter Wissenskonflikte Am Beispiel einer Debatte um rassistische Begriffe im Sommer 2022 - Richter, Susanne (Verhandlungen des 41. Kongresses der Deutschen Gesellschaft für Soziologie in Bielefeld 2022)

Ludwig Baumann - Ried, Dennis (Blick in die Geschichte. Karlsruher stadthistorische Beiträge)

Speech Disentanglement for Analysis and Modification of Acoustic and Perceptual Speaker Characteristics - Rautenberg, Frederik; Kuhlmann, Michael; Ebbers, Janek; Wiechmann, Jana; Seebauer, Fritz; Wagner, Petra; Haeb-Umbach, Reinhold (Fortschritte der Akustik - DAGA 2023)

Comparing Humans and Algorithms in Feature Ranking: A Case-Study in the Medical Domain - Hanselle, Jonas; Kornowicz, Jaroslaw; Heid, Stefan; Thommes, Kirsten; Hüllermeier, Eyke (Lernen, Wissen, Daten, Analysen (LWDA) Conference Proceedings)
The selection of useful, informative, and meaningful features is a key prerequisite for the successful application of machine learning in practice, especially in knowledge-intense domains like decision support. Here, the task of feature selection, or ranking features by importance, can, in principle, be solved automatically in a data-driven way but also supported by expert knowledge. Besides, one may of course, conceive a combined approach, in which a learning algorithm closely interacts with a human expert. In any case, finding an optimal approach requires a basic understanding of human capabilities in judging the importance of features compared to those of a learning algorithm. Hereto, we conducted a case study in the medical domain, comparing feature rankings based on human judgment to rankings automatically derived from data. The quality of a ranking is determined by the performance of a decision list processing features in the order specified by the ranking, more specifically by so-called probabilistic scoring systems.

Large Scale Scanning of TLS Session Ticket Confusion - Storm, Tim Leonhard
Session tickets are a resumption mechanism, which can speed up repeated TLS connections. To do so, information is stored client-side, encrypted with an additional symmetric key, which is separate from existing private keys. A server only has to store this key, making session tickets stateless for the server. If the key is shared between servers, a client can be misled into resuming a session with a different, less secure server. In this thesis, we design and implement a scan for detecting prerequisites to such an attack, by requesting and redeeming tickets for pair-wise servers. We find that 17,901 out of 22,127 scanned (virtual) hosts are potentially vulnerable to this attack because they share their keys and accept tickets issued for other domains. We discuss the difficulties of detecting such an attack and show that unfortunately, our approach does not scale to larger sample sizes.

LitCQD: Multi-Hop Reasoning in Incomplete Knowledge Graphs with Numeric Literals - Demir, Caglar; Wiebesiek, Michel; Lu, Renzhong; Ngonga Ngomo, Axel-Cyrille; Heindorf, Stefan (ECML PKDD)

Weiterbildung des Weiterbildungspersonals – Vorwiegend eine Aufgabe des Lernens am Arbeitsplatz - Schwede, Jana; Harteis, Christian (Nachhaltigkeitsorientierte Weiterbildungsdidaktik: Die doppelte Multiplikatorenqualifizierung)

Auswirkungen einer Online-Intervention (Mindset, Lerntechniken) auf den Studieneinstieg - Diederich, Malte; Spatz, Verena; Bauer, Anna Brigitte (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung (2022))

Intersektionalität und erzählte Welten – Einführung - Abrego, Verónica; Henke, Ina; Kißling, Magdalena; Lammer, Christina; Leuker, Maria-Th. (Intersektionalität und erzählte Welten. Fachwissenschaftliche und fachdidaktische Perspektiven auf Literatur und Medien)

Het verschil tussen strips en graphic novels (in Vlaanderen) - Lammer, Christina

Power-to-hydrogen and hydrogen-to-X energy systems for the industry of the future in Europe - Genovese, Matteo; Schlüter, Alexander; Scionti, Eugenio; Piraino, Francesco; Corigliano, Orlando; Fragiacomo, Petronilla (International Journal of Hydrogen Energy)
Keywords: Hydrogen economy; Green hydrogen; Power-to-X; Hydrogen-to-X; Sector coupling

Karneval und OWL - Breckner, Anne

Auszeit - Breckner, Anne

Übergang Schule-Beruf als Chancenverbesserungssystem – Zur Gestaltung von Lebensräumen und Entwicklung von Praktiken für den Übergang - Kremer, H.-Hugo; Otto, Franziska (bwp@ Berufs- und Wirtschaftspädagogik – online)
Sich wandelnde Bedingungen auf dem Ausbildungsmarkt, die daraus resultierenden veränderten Kompetenz- und Qualifikationsanforderungen sowie Anforderungen an eine lebensbegleitende berufliche Orientierung treffen insb. als (ausbildungs-)benachteiligt gekennzeichnete Jugendliche am Übergang Schule-Beruf. Jene Jugendliche münden in Maßnahmen des Übergangssystems wie die Ausbildungsvorbereitung (AV), wobei die konkreten Auswirkungen dieser Transformationsprozesse für diese Zielgruppe weitgehend unklar bleiben. In unserem Beitrag greifen wir die Überlegungen der Arbeitsgruppe 9+1 zum Übergangssystem verstanden als Chancenverbesserungssystem auf und diskutieren, was hierunter verstanden werden kann. Schließlich führen wir konkrete Anforderungen an das Chancenverbesserungssystem mit den Handlungsmöglichkeiten der Jugendlichen zusammen. Grundlegend verfolgen wir dabei nicht die Perspektive einer Anpassung der Jugendlichen an die Arbeitswelt, sondern fragen vielmehr danach, was Bildung leisten muss. Hierfür nehmen wir über qualitative Fallstudien die Perspektive der Jugendlichen sowie die Sichtweise des Bildungspersonals auf. In diesem Rahmen führen wir eine anforderungs- und subjektorientierte Perspektive zusammen und diskutieren u. a. anhand von Perspektiven auf das System, die curriculare Ebene, die Haltung der Bildungsakteur*innen, etc., was mit einer Gestaltung des Übergangssystems als Chancenverbesserungssystem konkret verbunden wäre.
Keywords: Übergangssystem; Selbstinszenierung; Chancenverbesserung; Subjektorientierung; Übergang Schule-Ausbildung

Open Data in musikphilologischen Projekten: Herausforderungen, Strategien, Potenziale - Kepper, Johannes; Münzmay, Andreas (DHd2023: Open Humanities, Open Culture)

Kirche und Musiktheater. Ein ambivalentes Verhältnis in Schlaglichtern - Adler, Luise; Tumat, Antje (Loccumer Pelikan. Religionspädagogisches Magazin für Schule und Gemeinde des Religionspädagogischen Instituts Loccum)

The Identification of a New Liquid Metal Embrittlement (LME) Type in Resistance Spot Welding of Advanced High-Strength Steels on Reduced Flange Widths - Yang, Keke; Meschut, Gerson; Seitz, Georg; Biegler, Max; Rethmeier, Michael (Metals (Special Issue Embrittlement Phenomena in Steel Metallurgy))

ProDaZ Online-Tool Technik - Heil, Rebekka; Prange, Sarah-Christin

ProDaZ Online-Tool Pflege. - Heil, Rebekka

Dynamic conformity assessment for joining force monitoring using Bayes filters - Butzhammer, Lorenz; Kappe, Fabian; Meschut, Gerson; Hausotte, Tino (Materials Research Proceedings)
Monitoring force-displacement or force-time curves is a widely used quality control technique in the field of mechanical joining. For online monitoring of self-piercing riveting, envelope curves are often used to define a tolerance zone for the measured setting force. However, the measurement uncertainty is typically not considered and the force curve of a joint can be wrongly rated as non-conform due to measurement errors and noise. In this article, we present a method for dynamical online filtering and uncertainty determination for noisy force curves using two types of Bayesian filters. The methodology is based on a Bayesian probability framework using a priori information for the process curve and sensor noise. To investigate the general feasibility of the method, force measurements with different noise levels are simulated and processed. The conformity is further assessed taking the uncertainty of the filtered signal into account. The results show that the Bayes filter technique is principally able to reduce noise for well-known characteristics of the process curve and sensor noise. Advantages over common filtering techniques, especially for experimental conditions with less known characteristics, are still to be verified. The methodology could be used in future for closed-loop controls to adapt process parameters dynamically.

Combination of versatile self-piercing riveting processes - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Materials Research Proceedings)
Due to economic and ecological framework conditions, a resource-saving utilization of raw materials and energy is becoming increasingly important in particular in the mobility sector. For the reduction of moving masses and the resources consumed, lightweight construction technologies are part of modern production processes in vehicle manufacturing, for example in the form of multi-material systems. Challenging in the manufacture of multi-material systems especially in view of changing supply chains is the variety of materials and geometries that bring conventional joining processes to their limits. Therefore, new processes are required, which can react versatile to process and disturbance variables. A widely used industrial joining process is semi-tubular self-piercing riveting, which is however a rigid process. To increase the versatility, the two newly established processes multi-range self-piercing riveting and tumbling self-piercing riveting are combined and the capabilities for targeted material flow control are united. Therefore, an innovative two-stage process based on the combination is introduced in this paper. The rivet is set with the multi-range self-piercing riveting process with an overlap of the rivet head and then formed by a tumbling process. Further, a specific adaptation of the tumbling strategy is used to investigate the possibility of reducing cracks in the rivet head. Thereby, different tumbling strategies are used and similar geometric joint formations are achieved to compare the results.

On the Multimodal Resolution of a Search Sequence in Virtual Reality - Klowait, Nils (Human Behavior and Emerging Technologies)
In virtual reality (VR), participants may not always have hands, bodies, eyes, or even voices—using VR helmets and two controllers, participants control an avatar through virtual worlds that do not necessarily obey familiar laws of physics; moreover, the avatar’s bodily characteristics may not neatly match our bodies in the physical world. Despite these limitations and specificities, humans get things done through collaboration and the creative use of the environment. While multiuser interactive VR is attracting greater numbers of participants, there are currently few attempts to analyze the in situ interaction systematically. This paper proposes a video-analytic detail-oriented methodological framework for studying virtual reality interaction. Using multimodal conversation analysis, the paper investigates a nonverbal, embodied, two-person interaction: two players in a survival game strive to gesturally resolve a misunderstanding regarding an in-game mechanic—however, both of their microphones are turned off for the duration of play. The players’ inability to resort to complex language to resolve this issue results in a dense sequence of back-and-forth activity involving gestures, object manipulation, gaze, and body work. Most crucially, timing and modified repetitions of previously produced actions turn out to be the key to overcome both technical and communicative challenges. The paper analyzes these action sequences, demonstrates how they generate intended outcomes, and proposes a vocabulary to speak about these types of interaction more generally. The findings demonstrate the viability of multimodal analysis of VR interaction, shed light on unique challenges of analyzing interaction in virtual reality, and generate broader methodological insights about the study of nonverbal action.
Keywords: Human-Computer Interaction; General Social Sciences; Social Psychology; Virtual Reality : Multimodality; Nonverbal Interaction; Search Sequence; Gesture; Co-Operative Action; Goodwin; Ethnomethodology

First steps towards real-time assessment of attentional weights and capacity according to TVA - Banh, Ngoc Chi; Scharlau, Ingrid (Abstracts of the 65th TeaP)

Emerging disciplinary voices - Stock, Ingrid; Karsten, Andrea; Eik-Nes, Nancy Lea (Sakprosa)
While referencing is an important feature of academic writing, many students struggle with using sources. This struggle seems to be due, in part, to the tension students experience when advised to cite sources (i.e., others’ voices) on the one hand, and to demonstrate their own disciplinary voice on the other hand. The aim of this article is to contribute to the understanding of source use, presenting a figure that illustrates gradients of students’ engagement with sources in various sections of their bachelor’s theses. Based on Bakhtin’s idea that a writer’s voice gradually emerges out of others’ words, and the terms knowledge telling and knowledge transforming, we developed a continuum that might help to understand the complexity of source use. We arrived at this continuum through the qualitative exploration of students’ use of sources in 15 bachelor’s theses from the humanities in one Norwegian university. In this article, we illustrate the continuum through extracts from the students’ theses, showing how issues of voice are intertwined with students’ engagement with sources. We propose that understanding the various functions of sources as they are typically used in the disciplines will help students to develop and demonstrate their disciplinary voices. Moreover, the continuum provides a foundation for fruitful discussions of writing practices that raise critical awareness about implicit expectations concerning source use and issues of voice in academic writing.
Keywords: Automotive Engineering

Voices in Dialogue: Taking Polyphony in Academic Writing Seriously - Karsten, Andrea (Written Communication)
In the past decades, the notion of voice in the theorizing and teaching of academic writing has been the subject of much debate and conceptual change, especially concerning its relation to writer identity. Many newer accounts of voice and identity in academic writing draw on the dialogical concept of voice by Bakhtin. However, some theoretical and methodological inconsistencies have surfaced in the adaptions of the concept. Working from a refinement of the dialogical notion of voice based on the concepts of polyphony and interiorization, this article presents a methodological approach for analyzing voice(s) in writing. The article presents material around the evolution of an early-career researcher’s dissertation synopsis. The material is multilayered, including the writer’s text, transcripts from an interdisciplinary peer-feedback conversation with two colleagues, and a video-stimulated interview with the writer. Excerpts of the material were analyzed to trace the polyphony of interiorized voices that influenced the writing. This focus revealed the multivoicedness of academic texts as an effect of their history of coming into being. This article contributes to the question of voice and identity in academic writing from a dialogical psycholinguistic perspective by presenting a de-reifying notion of voice grounded in an understanding of writing as a polyphonic activity, which also feeds into the formation of a writer’s self.
Keywords: Literature and Literary Theory; Communication

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Halogen-Free Flame Retardant Powder Materials for Laser Sintering: Evaluation and Process Stability Analysis - Neitzel, Fabian; Kletetzka, Ivo; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
The high flammability of components manufactured by laser sintering (LS) using standard polyamide 12 (PA12) powder still severely restricts their use in industries such as electronics, aviation, and transportation. A key factor for the further establishment of LS is the expansion of the material portfolio with, for example, refreshable and halogen-free flame-retardant (FR) powder materials. Accordingly, various halogen-free FRs are investigated in this work and evaluated with respect to their use in LS. First, their decomposition behavior and mode of action are examined. Subsequently, the additives are dry blended with PA12 to investigate properties relevant for LS, such as particle morphology, thermal behavior and melt viscosity. Afterwards, test specimens for UL94 vertical flame-retardancy tests are produced by processing the dry blends on an EOS P3 LS system. Finally, the process stability of the process-aged powder blends is investigated by again examining the thermal behavior and melt viscosity.
Keywords: Additive Manufacturing; Laser Sintering; Flame Retardant; Polyamide 12

Coworking - Krause, Ina (Arbeit)
Zusammenfassung Der Beitrag beschäftigt sich mit dem Konzept Coworking und arbeitet auf Basis eigener empirischer Daten heraus, wie dieses Konzept im Zuge seiner wachsenden Verbreitung und der Etablierung von Coworking-Spaces als ‚dritten Orten der Arbeit‘ Legitimität für neue Gestaltungsideen und Wertvorstellungen von Büroarbeit generiert. Coworking-Spaces werden dabei als ‚dritte Orte‘ definiert, die dem Raumkonzept der Schaffung einer flexibel anpassbaren und Kreativität fördernden Arbeitsumgebung für Büroarbeiter:innen folgen. Das Geschäftskonzept Coworking-Space wird inzwischen aber auch als alternatives Organisationsmodell von Arbeit wahrgenommen. Dem Beitrag liegt das Forschungsinteresse zugrunde zu erkunden, wie und in welchen Variationen das Konzept Coworking in Büroarbeitsorganisationen, die sich selbst als Coworking-Space bezeichnen, adaptiert und praktisch umgesetzt wird. Nachgezeichnet wird, inwiefern Coworking als alternatives Gestaltungsmodell oder, im Sinne von Meyer und Rowan, Rationalisierungskonzept der Organisation von Arbeit Elemente eines neuen Normalitätsverständnisses von Büroarbeit generiert, welches über Betreiber:innen von Coworking-Spaces und Coworker:innen inzwischen in die Breite der Arbeitsgesellschaft getragen wird.
Keywords: Industrial and Manufacturing Engineering

Im Osten nichts Neues? Über (un)bekannte Akteure in der regionalen Weiterbildungslandschaft. - Krause, Ina; Biess, Anne; Bohlinger, Sandra (bwp@ Berufs- und Wirtschaftspädagogik – online)

Entkoppelte Arbeitswelten - Krause, Ina
Die Strukturen der industriell geprägten Arbeitsgesellschaft werden durch den zunehmenden Einsatz automatisierter und digitaler Technologien sowie den Ausbau der Infrastruktur des Internets maßgeblich verändert. Gleichzeitig lässt sich eine intensive Flexibilisierung vertrauter Strukturen betriebszentrierter Organisationsformen von Beschäftigung beobachten. Ina Krause beschreibt einzelne Dynamiken auf der gesellschaftlichen Mesoebene und trägt damit zur Debatte über die nachhaltige Gestaltung der digitalen und virtuellen Arbeitsgesellschaft in Deutschland bei.

Frontmatter - Krause, Ina; Jacobsen, Heike; Gerhards, Christian (Arbeit)
Keywords: Industrial and Manufacturing Engineering

Turnover-Based Corporate Income Taxation and Corporate Risk-Taking - Amberger, Harald; Siahaan, Fernando; Sureth-Sloane, Caren

Business Reputation Systems based on Blockchain Technology—A Risky Advance - Hemmrich, Simon (Proceedings of 31st European Conference on Information Systems (ECIS 2023))
Reputation is indispensable for online business since it supports customers in their buying decisions and allows sellers to justify premium prices. While IS research has investigated reputation systems mainly as review systems on online platforms for business-to-consumer (B2C) transactions, no proper solutions have been developed for business-to-business (B2B) transactions yet. We use blockchain technology to propose a new class of reputation systems that apply ratings as voluntary bonus payments: Before a transaction is performed, customers commit to pay a bonus that is granted if a service provider has performed a service properly. As opposed to rival reputation systems that build on cumulated ratings or reviews, our system enables monetized reputation mechanisms that are inextricably linked with online transactions. We expect this system class to provide more trustworthy ratings, which might reduce agency costs and serve quality providers to establish a reputation towards new customers, building on second-order trust.
Keywords: Trust; Risk; Reputation System; Blockchain Technology; Business Reputation System.

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

The role of digital technologies in transforming student learning landscapes - Rezat, Sebastian; Geiger, Vince (Handbook of Digital Resources in Mathematics Education)

Implementing profession orientation as a design principle for overcoming Klein’s second discontinuity – preservice teacher’s perspectives on interface activities in the context of a geometry course - Hoffmann, Max; Biehler, Rolf (ZDM – Mathematics Education)
Intending to counteract Klein’s second discontinuity in teacher education, we explored and applied the innovation of “interface ePortfolio” in the context of a geometry course for preservice teachers (PSTs). The tool offers the possibility of implementing the design principle of profession orientation. In the article, we theoretically clarify what we understand by this principle and locate our innovative concept against this theoretical background. We empirically investigate the extent to which counteraction against the second discontinuity is successful by analyzing reflection texts created in the interface ePortfolio, focusing on PSTs’ perspectives. Our qualitative content analysis shows that most of them perceive the innovation as helpful in the intended sense and indicates that the course concept, in general, and the interface ePortfolio, in particular, have helped establish relevant links between the course content and their later work as teachers.
Keywords: General Mathematics; Education

Towards comparable ratings: Exploring bias in German physician reviews - Kersting, Joschka; Maoro, Falk; Geierhos, Michaela (Data & Knowledge Engineering)
In this study, we evaluate the impact of gender-biased data from German-language physician reviews on the fairness of fine-tuned language models. For two different downstream tasks, we use data reported to be gender biased and aggregate it with annotations. First, we propose a new approach to aspect-based sentiment analysis that allows identifying, extracting, and classifying implicit and explicit aspect phrases and their polarity within a single model. The second task we present is grade prediction, where we predict the overall grade of a review on the basis of the review text. For both tasks, we train numerous transformer models and evaluate their performance. The aggregation of sensitive attributes, such as a physician’s gender and migration background, with individual text reviews allows us to measure the performance of the models with respect to these sensitive groups. These group-wise performance measures act as extrinsic bias measures for our downstream tasks. In addition, we translate several gender-specific templates of the intrinsic bias metrics into the German language and evaluate our fine-tuned models. Based on this set of tasks, fine-tuned models, and intrinsic and extrinsic bias measures, we perform correlation analyses between intrinsic and extrinsic bias measures. In terms of sensitive groups and effect sizes, our bias measure results show different directions. Furthermore, correlations between measures of intrinsic and extrinsic bias can be observed in different directions. This leads us to conclude that gender-biased data does not inherently lead to biased models. Other variables, such as template dependency for intrinsic measures and label distribution in the data, must be taken into account as they strongly influence the metric results. Therefore, we suggest that metrics and templates should be chosen according to the given task and the biases to be assessed.
Keywords: Language model fairness; Aspect phrase classification; Grade prediction; Physician reviews

Verifying Software and Reconfigurable Hardware Services - Wehrheim, Heike; Platzner, Marco; Bodden, Eric; Schubert, Philipp; Pauck, Felix; Jakobs, Marie-Christine (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

On-The-Fly Computing -- Individualized IT-services in dynamic markets - Haake, Claus-Jochen; Meyer auf der Heide, Friedhelm; Platzner, Marco; Wachsmuth, Henning; Wehrheim, Heike
In the proposal for our CRC in 2011, we formulated a vision of markets for IT services that describes an approach to the provision of such services that was novel at that time and, to a large extent, remains so today: „Our vision of on-the-fly computing is that of IT services individually and automatically configured and brought to execution from flexibly combinable services traded on markets. At the same time, we aim at organizing markets whose participants maintain a lively market of services through appropriate entrepreneurial actions.“ Over the last 12 years, we have developed methods and techniques to address problems critical to the convenient, efficient, and secure use of on-the-fly computing. Among other things, we have made the description of services more convenient by allowing natural language input, increased the quality of configured services through (natural language) interaction and more efficient configuration processes and analysis procedures, made the quality of (the products of) providers in the marketplace transparent through reputation systems, and increased the resource efficiency of execution through reconfigurable heterogeneous computing nodes and an integrated treatment of service description and configuration. We have also developed network infrastructures that have a high degree of adaptivity, scalability, efficiency, and reliability, and provide cryptographic guarantees of anonymity and security for market participants and their products and services. To demonstrate the pervasiveness of the OTF computing approach, we have implemented a proof-of-concept for OTF computing that can run typical scenarios of an OTF market. We illustrated the approach using a cutting-edge application scenario – automated machine learning (AutoML). Finally, we have been pushing our work for the perpetuation of On-The-Fly Computing beyond the SFB and sharing the expertise gained in the SFB in events with industry partners as well as transfer projects. This work required a broad spectrum of expertise. Computer scientists and economists with research interests such as computer networks and distributed algorithms, security and cryptography, software engineering and verification, configuration and machine learning, computer engineering and HPC, microeconomics and game theory, business informatics and management have successfully collaborated here.

Compute Centers I: Heterogeneous Execution Environments - Hansmeier, Tim; Kenter, Tobias; Meyer, Marius; Riebler, Heinrich; Platzner, Marco; Plessl, Christian (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Flexible Industrial Analytics on Reconfigurable Systems-On-Chip - Boschmann, Alexander; Clausing, Lennart; Jentzsch, Felix; Ghasemzadeh Mohammadi, Hassan; Platzner, Marco (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Mikroformen des Praxisbezugs im Lehramtsstudium in NRW. Eine Bestandsaufnahme anhand der bildungswissenschaftlichen Studienanteile des Studiengangs HRSGe - Homt, Martina (die hochschullehre)
Im Zusammenhang mit dem Lehramtsstudium wird häufig ein mangelnder Praxisbezug kritisiert und dabei vornehmlich auf schulische Praxisphasen als sogenannte Makroformen des Praxisbezugs rekurriert. Eine Auseinandersetzung mit Mikroformen auf der curricularen Ebene findet hingegen kaum statt. Um einen Überblick über Mikroformen des Praxisbezugs zu erhalten, wird unter Rück griff auf Zielperspektiven der Lehrkräftebildung ein Analyserahmen mit den Kategorien Praxis als Bezugspunkt von Themen, Praxis als Gegenstand der Auseinandersetzung mit Themen, Praxis als Gegenstand von Erprobung sowie Praxis als Gegenstand von Analyse und Reflexion entwickelt und auf das intendierte Curriculum der lehramtsausbildenden Hochschulen in NRW in Form von Prüfungsordnungen als rahmensetzende Grundlage für die Planung von Studienangeboten angewandt. Die inhaltsanalytische Auswertung zeigt, dass alle Kategorien in den Prüfungsordnungen thematisiert werden, jedoch in unterschiedlicher Intensität. Die Befunde werden mit Blick auf die Zielperspektiven des Lehramtsstudiums, die begriffliche Unschärfe von Praxisbezug sowie Konsequenzen für die Ausgestaltung des Studienangebots auf Ebene des implementierten Curriculums diskutiert.

Tiere in der Theologie? Zur Überwindung der Tiervergessenheit. Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften - Herdramm, Henrike (BloKK. Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften)

Ästhetik digitaler Medien. Aktuelle Perspektiven - Flath, Beate

Gegen das Verstummen. Texthermeneutische Reflexionen zu Ironie in der Textsortenwelt des Gettos Litzmannstadt - Markewitz, Friedrich
Unmittelbar nach der nationalsozialistischen Machtergreifung setzte eine umfassende gesellschaftliche, juristische und existentielle Ausgrenzung jüdischer Akteure ein. Dem Zerbrechen bisheriger Welt- und Normverständnisse zu begegnen wurde zu einer existentiellen Herausforderung sowie zu einem notwendigen Bedürfnis. Eine wichtige Strategie war der Einsatz von Humor und Ironie; auch für die Menschen des Gettos Litzmannstadt. Aus texthermeneutischer, kulturlinguistischer und sprachphilosophischer Perspektive erfasst Friedrich Markewitz – unter Berücksichtigung des Gettos als Diskursraum und dessen Textsortenwelt – Verwendungsweisen und -funktionen von Ironie und perspektiviert sie, um so einen Beitrag zur linguistischen Aufarbeitung der Kommunikation jüdischer Akteure während der Shoa zu leisten.

Kommunikative Praktiken im Nationalsozialismus
Die nationalsozialistische Gesellschaft war geprägt von vielgestaltigen kommunikativen Praktiken des sozialen und auch gewaltvollen Ein- und Ausschlusses. Gleichzeitig bildeten sich durch Widerstandshandlungen vielfältige Gegendiskurse heraus. Der Sammelband nimmt konkrete Beispiele kommunikativer Praktiken während des Nationalsozialismus in den Blick und fragt speziell danach, inwiefern diese themen-, textsorten- und akteursspezifisch gebunden waren

„Die Juden 'leben' bei ihrer betont rechnerischen Begabung am längsten schon nach dem Rasseprinzip, weshalb sie sich auch am heftigsten gegen die uneingeschränkte Anwendung zur Wehr setzen“ - Pragmalinguistische Perspektiven auf kommunikative Ausgrenzungs- und Invektivitätspraktiken in der veröffentlichen wie unveröffentlichten textgebundenen Kommunikation Martin Heideggers - Markewitz, Friedrich (Kommunikative Praktiken im Nationalsozialismus)
Invektivitäts-, Aggressions- und Gewaltpraktiken sind als sozial-kommunikative zugleich universelle Phänomene. Als kommunikative Praktiken bestimmt, können sie direkte An- griffe, z. B. in Form rassistischer und sexistischer Kommentare, aber auch indirektere Formen und Muster der Ab- wie Ausgrenzung umfassen. Ziel des Beitrags ist die Erfassung, Einordnung und Kategorisierung kommunikativer Invektivitätshandlungen in den tex- tuellen Kommunikaten Martin Heideggers. Die Linguistik kann in diesem Kontext pro- duktiv dazu beitragen, die Umfassenheit, Ausdifferenziertheit und strukturelle Relevanz der Invektivitäts- wie Gewaltsprachhandlungen als kommunikative Praktiken dieses Phi- losophen aufzuarbeiten und würde dahingehend auf bestehende Forschungsdesiderata reagieren, da sich trotz der Affinität Heideggers zu Fragen des Sprachlichen bisher kaum sprachwissenschaftliche Analysen finden, die Heidegger(s Schriften) zum Analysegegen- stand hatten. Dabei sollen nicht nur explizite Formen kommunikativen Invektivitätshan- delns erfasst werden, sondern ebenso indirektere Formen der Exklusion und Antihuma- nität, die als Teil des differenzphilosophischen Programms Heideggers als Ausgrenzungs- erfahrungen reflektiert werden können.

Zur Verwendung von wörtlicher und imaginierter (Gegen-)Rede in Tarnschriften des kommunistischen und sozialistischen Widerstands - Markewitz, Friedrich; Wilk, Nicole M. (Kommunikative Praktiken im Nationalsozialismus)
Der Beitrag bestimmt anhand der für den kommunistischen und sozialistischen Wider- stand gegen die Hitler-Diktatur charakteristischen Textgattung Tarnschrift die für den Widerstandskontext noch nicht untersuchten kommunikativen Praktiken des Gegenre- dens. Gegenreden wird in seiner dialogischen und responsiven Qualität sowohl aus text- typologischer Perspektive beschrieben als auch am Beispiel der Re-Inszenierung durch direktes und indirektes Referat interaktionslinguistisch gefasst. Schließlich werden auf- grund dieser kritischen, opponierenden und teilweise ironisierenden Bezugnahmen von Tarnschriftenartikeln auf Inhalte des NS-Diskurses und der Propaganda Tarnschriften als kommunikative Gattung der Gegenrede bestimmt. Die kommunikative Praktik des Ge- genredens wird dahingehend präzisiert, dass sie strukturell eine »Ursprungsrede« insze- niert und ein Verfahren der Gegenrede beinhaltet, mit dem sich eine widerstandsspezifi- sche Diskursposition oft auch durch das Aufdecken von Widersprüchen vollzieht. In einer Korpusanalyse von 125 Tarnschriften wird die Varianz der dialogischen Gestaltungsver- fahren des Gegenredens anhand von redeanzeigenden Verben und redebezeichnenden Nomen als Kookkurrenten von Namen wichtiger NS-Funktionäre erfasst.

“Er ist doch ohne Übertreibung die Personifikation des Kategorischen Imperativs. Possibilities and limits of inner-discourse critique on the basis of selected textual communicates of the Litzmannstadt ghetto - Markewitz, Friedrich (Proceedings of the Conference Language and Power)
While forms of resistance and criticism of Nazi actors by jewish prisoners in concentration camps and jewish ghetto inhabitants have already been described, linguistic analyses of communicative conflicts within ghettos are still mostly lacking. Conflicts existed not only because of the heterogeneous social, ethnic, etc. compositions of the ghettos, but also because of internal power struggles. A power hierarchy arising from these struggles within the ghetto can be demonstrated for the Polish ghetto Litzmannstadt: a “ghetto elite” stood in sharp contrast to the majority of the ghetto population. In the context of this proceedings paper, the possibilities and limits of inner-discursive forms of critique on the basis of the power-axis “ghetto-elite”-ghetto-population will be reflected. During this, a contrastive perspective will be additionally adopted in order to compare different text genres, such as the diary, but also the ghetto chronicle and the ghetto encyclopedia, which are unique to the Litzmannstadt ghetto. These texts differ, among other things, in their degree of publicity and thus offer the possibility of being able to grasp the various conditions, functions, possibilities and limits of inner- discursive criticism of power.

Einleitung - Markewitz, Friedrich; Scholl, Stefan; Schubert, Katrin; Wilk, Nicole M. (Kommunikative Praktiken im Nationalsozialismus)

Der Text - Markewitz, Friedrich (Journal für Medienlinguistik)

Pantheon - Süßmann, Johannes

Mutation Tree Reconstruction of Tumor Cells on FPGAs Using a Bit-Level Matrix Representation - Opdenhövel, Jan-Oliver; Plessl, Christian; Kenter, Tobias (Proceedings of the 13th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies (HEART))

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 10,2: Zettelsammlung aus den Synopsen der Manuskriptbände I bis X, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2023, xv, 229–475 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete, Zbl. 1527.01035)